Intervención del terapista respiratorio en paciente masculino de 7 años de edad con asma bronquial. - Tacle Vera, Diana Carolina (2022)
Bronchial Asthma is a pathology of chronic evolution that produces inflammation and narrowing of the airways, characterized by variable and reversible airflow obstruction, causing signs of chest tightness, presence of wheezing on auscultation, dyspnea and cough without expectoration. The general objective of this clinical analysis was to determine an adequate treatment by the respiratory therapist for the pathology presented by the pediatric male patient, and at the same time to guarantee a favorable evolution.